Analysis of Character Factors Generation Z Career Choice in Lumajang District - Zulfikar, Mochammad Reza; Ghifary, Muhammad Tahajuddi (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study aims to analyze the characteristic factors influencing career choices among Generation Z, specifically in Lumajang Regency, East Java Province, with a case study at PT LABP. Generation Z, known as digital natives, has unique characteristics in determining their career choices. This research employs a quantitative approach using survey methods and multiple linear regression analysis to identify the influence of factors such as familiarity with technology, work values and attitudes, job flexibility, and the impact of social media on their career decisions. The findings indicate that familiarity with technology has a negative impact on the tendency to choose conventional careers, whereas job flexibility is a key determinant of Generation Z’s career choices. Additionally, social media plays a crucial role in shaping their job preferences. This study provides insights for companies and policymakers to enhance understanding and adaptation of recruitment strategies and career development plans to attract and retain Generation Z talent.